Predicting response to cognitive behavioral therapy in contamination-based obsessive–compulsive disorder from functional magnetic resonance imaging - Olatunji, B. O.; Ferreira-Garcia, R.; Caseras, X.; Fullana, M. A.; Wooderson, S.; Speckens, A.; Lawrence, N.; Giampietro, V.; Brammer, M. J.; Phillips, M. L.; Fontenelle, L. F.; Mataix-Cols, D. (Psychological medicine, 2014)
Although cognitive behavioral therapy (CBT) is an effective treatment for obsessive-compulsive disorder (OCD), few reliable predictors of treatment outcome have been identified. The present study examined the neural correlates of symptom improvement with CBT among OCD patients with predominantly contamination obsessions and washing compulsions, the most common OCD symptom dimension. Participants consisted of 12 OCD patients who underwent symptom provocation with contamination-related images during functional magnetic resonance imaging (fMRI) scanning prior to 12 weeks of CBT. Patterns of brain activity during symptom provocation were correlated with a decrease on the Yale-Brown Obsessive Compulsive Scale (YBOCS) after treatment, even when controlling for baseline scores on the YBOCS and the Beck Depression Inventory (BDI) and improvement on the BDI during treatment. Specifically, activation in brain regions involved in emotional processing, such as the anterior temporal pole and amygdala, was most strongly associated with better treatment response. By contrast, activity in areas involved in emotion regulation, such as the dorsolateral prefrontal cortex, correlated negatively with treatment response mainly in the later stages within each block of exposure during symptom provocation. Successful recruitment of limbic regions during exposure to threat cues in patients with contamination-based OCD may facilitate a better response to CBT, whereas excessive activation of dorsolateral prefrontal regions involved in cognitive control may hinder response to treatment. The theoretical implications of the findings and their potential relevance to personalized care approaches are discussed.